The Suitability of Faculty Performance to Student Graduate Profiles: A Tracing Study of IIM Surakarta Students - Uswatun Khasanah (Tarbawi, 2022)
This study aims to determine the suitability of the work fields of IIM Surakarta graduates in improving the quality and relevance of the higher education curriculum. This quantitative descriptive research uses a survey approach. In general, the implementation of this tracer study includes three steps: 1) development of concepts and instruments; 2) data collection; 3) data analysis and reporting. This research was conducted at the Faculty of Tarbiyah IIM Surakarta. Respondents and samples consisted of 25 graduates drawn from a total population of 110 graduates. The primary data in this study were all respondents who were taken randomly (random sampling). As for secondary data, researchers took scientific research sources in books, journals, proceedings, and others. Data were obtained by making an online questionnaire, and the results of data collection were then analyzed. At the same time, the study results revealed that the alumni's assessment of the performance of the Tarbiyah Faculty IIM Surakarta was from 25 respondents and consisted of nine indicators, 67% very good, 25% good, and 7% adequate. Absorption data revealed that 100% of alumni have worked and are spread across various fields for 60% of teachers, 16% of lecturers, 8% of company employees, 4% of civil servants, and 12% of the private sector. Alumni satisfaction data also show very good numbers. Furthermore, the relevance of the curriculum at the Tarbiyah Faculty includes 1) Alumni assessment of the suitability of lecture material with the work they are engaged in, showing 79% of alumni assessing the suitability of course material and work > 86%. A total of 17% stated that the suitability was 76%-85%, while 4% stated that the suitability was less than 50%. 2) Most alumni need information technology and English language skills in the workplace. 3) Get input and suggestions from alumni. The tracer study results for IIM Surakarta graduates shows a good category. The types of work are diverse but are dominated by education. The relevance of the Tarbiyah Faculty IIM curriculum is quite good, especially in terms of technical ability, confidence, and theoretical knowledge.